2011
DOI: 10.1007/s00384-011-1270-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing appropriateness for elective colorectal cancer surgery: clinical, oncological, and quality-of-life short-term outcomes employing different treatment approaches

Abstract: Laparoscopic and robotic surgeries for colorectal cancer present both the same advantages in comparison to open procedures in terms of faster recovery. However, our data do not seem to support the routine use of RCO as a cost-effective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 29 publications
4
97
0
1
Order By: Relevance
“…After this process, the reviewers identified 10 studies for a comprehensive review. Three studies were excluded according to the inclusion criteria192021, leaving 7 studies that were included in our analysis22232425262728. The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After this process, the reviewers identified 10 studies for a comprehensive review. Three studies were excluded according to the inclusion criteria192021, leaving 7 studies that were included in our analysis22232425262728. The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is evidence that shows our objective decision making in any case to perform any type of minimally invasive rectal resection. Bertani et al 23 suggested that use of a robotic platform for colectomy increases hospital expenses compared to conventional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to morbidity, none of the previous reports comparing RCS and OCS were able to show a significant decrease in complications [5][6][7][8][9][10][11] . This study also found that the frequency of major postoperative complications (ClavienDindo III/IV) did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned previously, there are only a few studies comparing RCS and OCS [5][6][7][8][9][10][11] . Interestingly, these reports came exclusively from tertiary centers in Korea and Italy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation